Continuous-Flow Reactions Mediated by Main Group Organometallics - Harenberg, Johannes H.; Weidmann, Niels; Knochel, Paul (Synlett, 2020)
The generation of reactive organometallic reagents in batch is often complicated by the low thermal stability of these important synthetic intermediates and can require low reaction temperatures and special reaction conditions. However, the use of continuous-flow setups and microreactors has led to a revolution in this field. In this short review, an overview is given of recent advances in this area, with a focus on the main group organometallics of Li, Na, and K.
Keywords: flow chemistry; organolithium compounds; organosodium compounds; organomagnesium compounds; Barbier conditions